Nutrient removal from high ammonium swine wastewater in upflow microaerobic biofilm reactor suffered high hydraulic load. (1st March 2019) - Meng, Jia; Li, Jiuling; He, Jiamin; Li, Jianzheng; Deng, Kaiwen; Nan, Jun
Abstract: To understand the ability of an upflow microaerobic biofilm reactor (UMBR) to remove nutrient from manure-free swine wastewater rich in NH4 + with a COD/TN ratio less than 1.00, effect of hydraulic loading rate (HLR) on the microaerobic process was evaluated with a constant reflux ratio of 25 at 25 °C. The results showed that changes in HLR had a remarkable effect on the performance of the UMBR in nutrient removal from the wastewater. With the favorable HLR 3.0 m 3 /(m 3 ·d) (Hydraulic Retention Time (HRT) 8 h), average removal of COD, NH4 + and TN in the microaerobic process reached 59.3%, 87.7% and 84.7%, respectively, though the COD/TN ratio was as low as 0.84. With an over HLR of 4.0 m 3 /(m 3 ·d) (HRT decreased to 6 h), bad performance of the UMBR was observed with an average removal of COD, NH4 + and TN as low as 45.0%, 59.0% and 57.5%, respectively. Since the HLR was decreased to 2.4 m 3 /(m 3 ·d) (HRT 10 h), the microaerobic process regained the efficiency in nutrient removal with a removal of COD, NH4 + and TN averaged 59.0%, 95.3% and 87.8%, respectively. The microaerobic condition allowed anammox bacteria, ammonia-oxidizing bacteria and archaea, nitrite-oxidizing bacteria and denitrifiers to all thrive in the UMBR, resulting in the efficient synchronous removal of organic carbon and nitrogen. As the dominant approach to nitrogen removal, anaerobic ammonium oxidation (anammox) pathway contributing to the TN removal in the microaerobic process exceeded 59.5% at HLR 3.0 m 3 /(m 3 ·d). The results demonstrated that the UMBR can remove nitrogen and carbon from swine wastewater, with a suitable HLR. Graphical abstract: Image 108845 Highlights: An upflow microaerobic biofilm reactor was operated to treat swine wastewater. HRT had a remarkable influence on the nitrogen removal. A nitrogen removal up to 80% was achieved with a HRT no less than 8 h. Molecular biology revealed anammox as the dominated nitrogen removal pathway. NOB with lower DO affinity was outcompeted by AOB in microaerobic condition.